A PANEL ANALYSIS OF PROFITABILITY IN THE FRUIT AND VEGETABLE PROCESSING INDUSTRY IN SERBIA - Stojanka Dakić; Kristina Mijić (Ekonomika Poljoprivrede (1979), 2018)
The aim of this paper is to identify the factors that influence the proftability of selected companies within the fruit processing industry in Serbia. Proftability was measured through the accounting indicator of the rate of return on assets (ROA). Proftability of fruit and vegetable processing companies is positive but at relatively low level. In the capacity of independent variables were used the size of the enterprise, debt ratio, quick ratio, inventory, sales growth and capital turnover ratio. The analysis covers the period from 2007 to 2015 (9 years) and includes 198 observation of the companies from the fruit and vegetable processing industry in Serbia. Panel regression model was built. The results of the conducted panel analysis showed that the sales growth and capital turnover ratio showed a statistically signifcant impact on proftability as a measure of the success of companies in the feld of fruit and vegetable processing industry. The size of the company showed a statistically signifcant impact on the proftability at a level of signifcance of 10%.